2009
DOI: 10.1111/j.1365-3083.2008.02225.x
|View full text |Cite
|
Sign up to set email alerts
|

IC31®, a Two‐Component Novel Adjuvant Mixed with a Conjugate Vaccine Enhances Protective Immunity against Pneumococcal Disease in Neonatal Mice

Abstract: IC31® is a novel adjuvant which combines the immunostimulatory effects of an 11‐mer antibacterial peptide (KLKL5KLK) and a synthetic oligodeoxynucleotide (ODN1a) which is a Toll‐like receptor 9 agonist without containing cytosine phosphate guanine (CpG) motifs. The effects of IC31® on neonatal immune response to vaccination have not been reported. Neonatal mice were immunized once or twice with a Streptococcus pneumoniae serotype 1 polysaccharide conjugate containing Tetanus Toxoid (Pnc1‐TT) carrier protein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 37 publications
(60 reference statements)
0
20
1
Order By: Relevance
“…No protection was observed when IC31 was reduced to 15.75 nmol KLK and 0.63 nmol ODN1a (approximately one-sixth of the adult dose). This is in contrast to our results for neonatal immunization with PCV, where the lowest dose (15.75 nmol KLK and 0.63 nmol ODN1a) of IC31 resulted in protection levels similar to those found when the highest dose (90 nmol KLK and 3.6 nmol ODN1a) was used in combination with proteins, with the latter inducing even higher vaccine-specific Ab levels (31). This finding suggests that higher levels of protein-specific Abs than PPS-specific Abs may be required to provide full protection against pneumococcal disease, possibly due to less exposure of the proteins on the bacterial surface than the PPS.…”
Section: Fig 3 Ic31 Induces Higher and More Rapid Ab Responses To Allcontrasting
confidence: 56%
See 1 more Smart Citation
“…No protection was observed when IC31 was reduced to 15.75 nmol KLK and 0.63 nmol ODN1a (approximately one-sixth of the adult dose). This is in contrast to our results for neonatal immunization with PCV, where the lowest dose (15.75 nmol KLK and 0.63 nmol ODN1a) of IC31 resulted in protection levels similar to those found when the highest dose (90 nmol KLK and 3.6 nmol ODN1a) was used in combination with proteins, with the latter inducing even higher vaccine-specific Ab levels (31). This finding suggests that higher levels of protein-specific Abs than PPS-specific Abs may be required to provide full protection against pneumococcal disease, possibly due to less exposure of the proteins on the bacterial surface than the PPS.…”
Section: Fig 3 Ic31 Induces Higher and More Rapid Ab Responses To Allcontrasting
confidence: 56%
“…Results from human trials of IC31 showed that when combined with the TB vaccine candidate Ag85B-ESAT6, it was well tolerated and highly immunogenic, with strong Th1 responses persisting more than 2.5 years following vaccination (48). We have previously shown that IC31 enhances the murine neonatal Ab response to a monovalent PCV and improves protection against pneumonia and lung infection (31).…”
mentioning
confidence: 99%
“…In April 2011 Menectra was approved for use in infants over the age of 9 months but is not yet recommended by the CDC. Hence, well-tolerated effective adjuvants may enhance and accelerate immune responses to conjugate vaccines in neonates and infants (24,25,38), the age group most vulnerable to meningococcal disease. Mycobacterium bovis bacillus Calmette-Guérin (BCG) is administered to human neonates in many countries worldwide.…”
mentioning
confidence: 99%
“…CpG, a TLR9 agonist, can induce adult-like DC and T-cell activation, while failing to induce adult-like antibody (Ab) responses (22). IC31 (Intercell AG), a two-component adjuvant consisting of an antibacterial peptide and the TLR9 agonist ODN1a, when combined with a pneumococcal conjugate vaccine, enhances protective immunity in neonatal mice (23). A synthetic water-in-oil emulsion-based adjuvant, CRL-8941 (24), and complete Freund's adjuvant (CFA) (25), induced adult-like T H 1 immune responses in neonatal mice, indicated by induction of antigen-specific IgG2a antibodies (an indicator of a T H 1 response in BALB/c mice) and/or IFN-␥-secreting splenocytes.…”
mentioning
confidence: 99%